Aberrant overexpression of CD14 on granulocytes sensitizes the innate immune response in mDia1 heterozygous del(5q) MDS. - Keerthivasan, G; Mei, Y; Zhao, B; Zhang, L; Harris, C; Gao, J; Basiorka, A; Schipma, M; McElherne, J; Yang, J; Verma, A; Pellagatti, A; et al. (American Society of Hematology, 2014)
The myelodysplastic syndromes (MDSs) include a spectrum of stem cell malignancies characterized by an increased risk of developing acute myeloid leukemia. Heterozygous loss of chromosome 5q (del[5q]) is the most common cytogenetic abnormality in MDS. DIAPH1 is localized to 5q31 and encodes one of the formin proteins, mDia1, which is involved in linear actin polymerization. Mice with mDia1 deficiency develop hematologic features with age mimicking human myeloid neoplasm, but its role in the pathogenesis of MDS is unclear. Here we report that mDia1 heterozygous and knockout mice develop MDS phenotypes with age. In these mice, CD14 was aberrantly overexpressed on granulocytes in a cell-autonomous manner, leading to a hypersensitive innate immune response to lipopolysaccharide (LPS) stimuli through CD14/Toll-like receptor 4 signaling. Chronic stimulation with LPS accelerated the development of MDS in mDia1 heterozygous and knockout mice that can be rescued by lenalidomide. Similar findings of CD14 overexpression were observed on the bone marrow granulocytes of del(5q) MDS patients. Mechanistically, mDia1 deficiency led to a downregulation of membrane-associated genes and a specific upregulation of CD14 messenger RNA in granulocytes, but not in other lineages. These results underscore the significance of mDia1 heterozygosity in deregulated innate immune responses in del(5q) MDS.